Andres natur i vår kultur - Ødemark, John (Tidsskrift for kulturforskning, 2016)
The point of departure is a "totem pole" constructed to oppose the Belo Monte dam in 2012. The artefact was presented as a quotation from an indigenous Juruna tale.The article traces the tale to a printed collection of myths from the Xingú, ending in an eschatological register: "The day our people die out entirely, the sky will collapse". Further, it (i) analyzes how material and textual aspects and traces of folkloric and national discourse furnish conditions for global "green fantasies", and (ii) identifies a lack of concern with such historical traces of cultural contact and translations in recent trends in cultural theory associated with "perspectivism" and the "ontological turn".